UTILIZING “WORDWALLS’ AS AN ASSESSMENT TOOL FOR INDONESIAN JUNIOR HIGH SCHOOL STUDENTS - Lina Anisah (English Review: Journal of English Education, 2022)
The purpose of this research was to analyze students' perceptions of the use of interactive media Wordwall as an assessment tool at SMP Negeri 1 Kolaka. The design of this study used a study case design. The subjects in this study were students of class VIII G SMP Negeri 1 Kolaka, totaling 26 students in 2022. The collection technique used questionnaires and interviews. Questionnaires were given to determine students' perceptions and interviews were conducted to find out more in-depth answers so that researchers could describe and study optimally students' perceptions of the Wordwall application as an assessment tool. The results of this research indicate that 87,5% of students are interested in using the Wordwall application as an assessment tool. Easy use, attractive appearance, and varied questions make students want to use the Wordwall application as an assessment tool in the future.